Analysis of the distribution of gas turbine unit operation modes as a tool for improving the stability of the power system - Yavorskyi, Oleksandr; Tarakhtii, Olha; Zhukovskyi, Vladyslav; Panin, Viktor (Technology audit and production reserves, 2024)
The object of research is the optimal distribution of operating modes of gas turbine units (GTU) as a tool for increasing the stability of the Ukrainian power system in crisis situations. Given the challenges caused by the destruction of the energy infrastructure due to massive shelling, ensuring the stability of electricity supply requires the development of new approaches to frequency regulation. The frequency of electricity is a critical parameter that determines the balance between generation and consumption. Its violation can cause serious consequences, such as equipment shutdown and destabilization of the power system. The work was aimed at creating mathematical models of GTU and the power system, allowing to analyze the change in frequency and power depending on the operating modes. As well as at developing a methodology for optimal load distribution between units under conditions of variable external influences. The work describes in detail the structure of the GTU model in the Simulink environment, which takes into account dynamic processes in gas volumes, the combustion chamber and the rotor of the unit. The proposed methodology is based on the study of two approaches to power distribution: uniform and proportional to the control range of each GTU. A numerical experiment has shown that uniform distribution is better suited for positive disturbances, reducing the integral indicator (integral square error ISE) by 15 % compared to traditional methods, while for negative disturbances, proportional distribution demonstrates a decrease in ISE by 20 %. In the case of positive disturbances, uniform distribution for different combinations of capacities on average shows 0.6 % better control quality than the proportional approach, and for negative disturbances, proportional distribution on average shows 0.25 % better control quality, compared to uniform. The research results have significant practical potential and can be used to improve the control systems of the power systems of Ukraine in conditions of a shortage of generating capacities and crisis situations.